2016
DOI: 10.1371/journal.pone.0148225
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic Differentiation of Human Dental Pulp Stem Cells on Hydrogel Scaffolds Derived from Decellularized Bone Extracellular Matrix and Collagen Type I

Abstract: ObjectivesThe aim of this study was to evaluate the level of odontogenic differentiation of dental pulp stem cells (DPSCs) on hydrogel scaffolds derived from bone extracellular matrix (bECM) in comparison to those seeded on collagen I (Col-I), one of the main components of dental pulp ECM.MethodsDPSCs isolated from human third molars were characterized for surface marker expression and odontogenic potential prior to seeding into bECM or Col-I hydrogel scaffolds. The cells were then seeded onto bECM and Col-I h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 48 publications
2
89
0
1
Order By: Relevance
“…Cells encapsulated in dECM hydrogels showed a higher proliferation rate than those in demineralized bone or collagen type I hydrogels. Paduano et al demonstrated that dental pulp stem cells (DPSCs), when seeded on dECM derived from bovine tibia, underwent odontogenic differentiation in vitro . Adding exogenous growth factors such as basic fibroblast growth factor (bFGF) and epidermal growth factor (EGF) to dECM hydrogels had a synergistic effect on the degree of differentiation .…”
Section: Postdecellularization Processing Methodsmentioning
confidence: 99%
“…Cells encapsulated in dECM hydrogels showed a higher proliferation rate than those in demineralized bone or collagen type I hydrogels. Paduano et al demonstrated that dental pulp stem cells (DPSCs), when seeded on dECM derived from bovine tibia, underwent odontogenic differentiation in vitro . Adding exogenous growth factors such as basic fibroblast growth factor (bFGF) and epidermal growth factor (EGF) to dECM hydrogels had a synergistic effect on the degree of differentiation .…”
Section: Postdecellularization Processing Methodsmentioning
confidence: 99%
“…The viability of cells cultured on the surface of ECM hydrogels in vitro has been consistently shown for cell lines [23, 54, 63, 64, 70, 71, 83], primary cells [57, 63, 69, 71, 75, 83, 85], and stem cells [44, 49, 50, 73, 82, 86]. In addition, the innate bioactivity of soluble factors within the ECM has been demonstrated using in vitro culture with media supplemented with solubilized ECM to remove the influence of hydrogel structure on the function of cells.…”
Section: Cellular Response To Ecm Hydrogelsmentioning
confidence: 99%
“…The differentiation into osteogenic lineage has already been demonstrated in DPSCs [27–29, 34] and a considerable mineral matrix deposition has been observed using innovative scaffolds for their culturing [35, 36]; moreover these cells, if cultured on β -tricalcium phosphate/poly (l-lactic acid/caprolactone) three-dimensional scaffolds, showed an increased osteogenesis in the presence of Vit D compared to dexamethasone [37]. …”
Section: Introductionmentioning
confidence: 99%